2015
DOI: 10.1111/bph.12999
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nrf2 activators from microbial transformation products inhibit blood–retinal barrier permeability in rabbits

Abstract: BACKGROUND AND PURPOSENuclear factor erythroid 2-related factor 2 (Nrf2) is a redox-sensitive transcription factor that binds to antioxidant response elements located in the promoter region of genes encoding many antioxidant enzymes and phase II detoxifying enzymes. Activation of the Nrf2 pathway seems protective for many organs, and although a well-known Nrf2 activator, bardoxolone methyl, was evaluated clinically for treating chronic kidney disease, it was found to induce adverse events. Many bardoxolone met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Using in vivo studies we demonstrated that oral administration of RS9 inhibits neovascularization in oxygen-induced retinopathy in rats, and an intravitreal injection of RS9 suppressed blood-retinal barrier permeability in glycated albumin-injected rabbits [53]. The chemical structure of RS9 is unique because it contains epoxidation in the A-ring and hydroxylation in the E-ring.…”
Section: Nrf2 Activators Ameliorate Oxidative Stress-related Retinmentioning
confidence: 99%
“…Using in vivo studies we demonstrated that oral administration of RS9 inhibits neovascularization in oxygen-induced retinopathy in rats, and an intravitreal injection of RS9 suppressed blood-retinal barrier permeability in glycated albumin-injected rabbits [53]. The chemical structure of RS9 is unique because it contains epoxidation in the A-ring and hydroxylation in the E-ring.…”
Section: Nrf2 Activators Ameliorate Oxidative Stress-related Retinmentioning
confidence: 99%
“…RS9 is a specific activator of Nrf2 (Nakagami et al . ,b). RS9 alters the permeability of the blood–retinal barrier and has cytoprotective effects in the retina of mice and rabbits (Nakagami et al .…”
mentioning
confidence: 99%
“…RS9 alters the permeability of the blood–retinal barrier and has cytoprotective effects in the retina of mice and rabbits (Nakagami et al . ,b). However, a more accurate determination of the mechanism(s) underlying the protective effects of RS9 must be made.…”
mentioning
confidence: 99%
“…RS9 and its microspheres were prepared as previously reported. 7 In brief, RS9 and poly-lactic acid in dichloromethane was poured into an aqueous solution for preparation of microspheres. With continuous stirring of the mixture, dichloromethane was evaporated, leaving solid RS9-containing microspheres.…”
Section: Methodsmentioning
confidence: 99%
“…We recently succeeded in obtaining a novel Nrf2 activator, RS9, and demonstrated that RS9 inhibits blood-retinal barrier permeability in rabbits. 7 The present study used optical coherence tomography (OCT) to examine the effectiveness of RS9 in inhibiting retinal degeneration in rhodopsin Pro347Leu rabbits.…”
Section: Introductionmentioning
confidence: 99%